PENGARUH LINGKUNGAN KERJA FISIK, MOTIVASI DAN KOMUNIKASI TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN DONGGALA - Damsjik, Rasfiani (Katalogis, 2017)
The intentions of study are: (1) to determine simultaneous influence of Physical Work Environment, Motivation, and Communication on Officials Satisfaction in the Regional Development Planning Agency of Donggala Regency, (2) to determine partial influence of Physical Work Environment on Officials Satisfaction in the Regional Development Planning Agency of Donggala Regency, (3) to determine partial influence of Motivation on Officials Satisfaction in the Regional Development Planning Agency of Donggala Regency, (4) to determine partial influence of Communication on Officials Satisfaction in the Regional Development Planning Agency of Donggala Regency. Method of analysis used is multiple linear regressions with 67 samples that are selected throught census technique. Based on the tests, the result cocludes that: 1) Physical Work Environment , Motivation, and Communication simultaneous have positive and significant influence satisfaction in the Regional Development Planning Agency of Donggala Regency; 2) Physical Work Environment has positive and significant influence satisfaction in the Regional Development Planning Agency of Donggala Regency; 3) Motivation, has positive and significant influence satisfaction in the Regional Development Planning Agency of Donggala Regency; 4) Simultaneous has positive and significant influence satisfaction in the Regional Development Planning Agency of Donggala Regency